2006
DOI: 10.1007/s00441-006-0214-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile and overexpression of apoptosis-related genes (NGFI-B and Gadd 45 γ) in early phase of Thy-1 nephritis model

Abstract: Mesangioproliferative glomerulonephritis (MPGN) is a disease of high incidence in humans. Rat Thy-1 nephritis (Thy-1 N), namely, anti-thymocyte serum (ATS)-induced nephritis, is considered to be an animal model for studying MPGN. Although previous studies have demonstrated that glomerular mesangial cell (GMCs) injury might be a feature of Thy-1 N, the mechanism of the disease (i.e., GMC apoptosis) remains unclear. We have examined the pathologic changes of GMCs and the gene expression profile of renal tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Several studies show that Gadd45 proteins not only induce cell G2/M arrest and inhibit cell entry into S phase, but also promote cell apoptosis [16][17][18][19]. Our previous microarray analysis detected the up-regulated expression of Gadd45g gene in the renal tissue of Thy-1N rats [20] and in GMC stimulated by sublytic C5b-9 complexes (unpublished data). However, the role of Gadd45g gene in GMC apoptosis of Thy-1N remains to be defined.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Several studies show that Gadd45 proteins not only induce cell G2/M arrest and inhibit cell entry into S phase, but also promote cell apoptosis [16][17][18][19]. Our previous microarray analysis detected the up-regulated expression of Gadd45g gene in the renal tissue of Thy-1N rats [20] and in GMC stimulated by sublytic C5b-9 complexes (unpublished data). However, the role of Gadd45g gene in GMC apoptosis of Thy-1N remains to be defined.…”
Section: Introductionmentioning
confidence: 78%
“…Our previous studies using gene microarray analysis revealed that the expression of Gadd45g gene was upregulated in the renal tissue of Thy-1N rats and in GMC stimulated by sublytic C5b-9 (unpublished data). Both mRNA and protein expression of Gadd45g detected by real-time PCR and IHC staining in the early phase of the GMC apoptosis in Thy-1N are remarkably increased [20], suggesting that up-regulation of Gadd45g expression may play a role in the GMC apoptosis. It is possible that the upregulation of Gadd45g expression is a mediator of GMC apoptosis.…”
mentioning
confidence: 95%
See 3 more Smart Citations